Unveiling the stressful experiences faced by asexual individuals in South Korea: a consensual qualitative study - An, Hyunju; Kim, Eunha (Psychology and Sexuality, 2024)
This qualitative study explores the stressful experiences faced by asexual individuals in South Korea. We conducted in-depth interviews with 12 South Korean adults who identified as asexual and analysed their data using consensus qualitative research. The analyses revealed 20 categories across five domains, including difficulties in defining and articulating asexual identity due to a lack of language and representation, facing denial and invalidation, navigating ambivalent experiences of invisibility, combating misconceptions, and encountering difficulties in connecting with asexual individuals and other members of the queer community. The study identified several stressors reported by South Korean asexual individuals, such as the dearth of language and representation regarding asexuality, lack of access to asexual networks, misconception that experiencing little or no sexual attraction is caused by a lack of love, casual use of the term ‘asexual’, and fear of increasing invisibility by concealing one’s asexual identity. Although these stressors have not been widely documented in other contexts, further research is needed to determine whether they are unique to the South Korean context. These findings highlight the need for greater awareness and understanding of asexuality in South Korea to promote the well-being and inclusion of asexual individuals.
Keywords: ace specturm; Asexuality; challenges; CQR; South Korea